CF3‐Containing para‐Quinone Methides for Organic Synthesis. Issue 25 (30th March 2020) - Winter, Michael; Schütz, Roman; Eitzinger, Andreas; Ofial, Armin R.; Waser, Mario
Abstract : A new family of CF3 ‐containing para ‐quinone methides (CF3 ‐QMs) was systematically investigated for its suitability in organic synthesis. Addition of different nucleophiles gives access to target molecules with a benzylic CF3 ‐containing stereogenic center straightforwardly. The electrophilicity parameter E of the prototypical CF3 ‐QM 2, 6‐di‐ tert ‐butyl‐4‐(2, 2, 2‐trifluoroethylidene)cyclohexa‐2, 5‐dien‐1‐one was determined to be –11.68 according to the Mayr scale, making it one of the most reactive quinone methides known so far. Abstract : Novel CF3 ‐containing para‐quinone methides were systematically investigated for their use in (asymmetric) transformations.